Intergovernmental relations on immigrant integration in Canada: Insights from Quebec, Manitoba, and Ontario. Issue 5 (20th October 2019) - Jeram, Sanjay; Nicolaides, Eleni
ABSTRACT: The pattern of intergovernmental relations (IGR) on immigrant integration in Canada runs counter to core arguments in the extant literature. In particular, Canada's federal structures have not produced multilateral, institutionalized, and conflictual IGR; IGR in Canada has been predominantly bilateral and only moderately institutionalized. Moreover, IGR has been conflictual at times, while collaborative at others. Several factors explain this unexpected pattern. In an attempt to ward off separatism, the central government devolved authority over immigrant selection and settlement programmes to Quebec, creating a deep asymmetry between Quebec and the Anglophone provinces (and territories) in these areas. Interprovincial competition drove other provinces to seek powers over immigration and integration. The central government – driven by fiscal pressures and a philosophical commitment to symmetry – struck bilateral agreements with Anglophone provinces to fund and devolve settlement programming and some control over the selection of economic immigrants.